2001
DOI: 10.1097/00007890-200105150-00015
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of Tauroursodeoxycholate During Harvesting and Cold Storage of Human Liver

Abstract: The use of TUDCA during harvesting and cold storage of human liver is associated with significant protection from ischemia-reperfusion injury. The clinical significance of this findings must be studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 31 publications
1
32
0
1
Order By: Relevance
“…Animal experiments have shown that parenteral donor pre-treatment with TUDCA reduces reperfusion injury as reflected by lower serum liver enzyme levels and better preservation of the bile duct, as seen in electron microscope studies [8,211. Similar results were obtained when TUDCA was administrated into the portal vein and/or added to the preservation solution [22].…”
Section: Discussionsupporting
confidence: 79%
“…Animal experiments have shown that parenteral donor pre-treatment with TUDCA reduces reperfusion injury as reflected by lower serum liver enzyme levels and better preservation of the bile duct, as seen in electron microscope studies [8,211. Similar results were obtained when TUDCA was administrated into the portal vein and/or added to the preservation solution [22].…”
Section: Discussionsupporting
confidence: 79%
“…29 Promising potential treatments include the replacement of hydrophobic bile salts with hydrophilic ones such as tauroursodeoxycholate to reduce both duct and hepatocyte injury. 21,30 The modulation of intracellular signaling pathways, such as the activation of nuclear factor KB, which has been shown to inhibit apoptosis by tumor necrosis factor alpha, may also find application in the ischemic liver. 31 Finally, based on the study of Vajdova et al, 32 the inclusion of energy substrates to the perfusion medium may allow for complete restoration of tissue ATP levels, thereby attenuating injury (Table 2).…”
Section: Early Intrahepatic Cholestatic Syndrome Ischemia/reperfusionmentioning
confidence: 99%
“…Thus, strategies aimed at modulating BI-1 as well as other component of ER stress-mediated apoptosis could protect not only against ER stress but also against the mitochondrial-dependent apoptosis pathway. In liver, the small molecule chemical chaperones, 4-PBA and Tauroursodeoxycholic acid (TUDCA) protect against I/R-induced ER stress-mediated cell death in non-steatotic livers undergoing ischemic conditions (Falasca et al, 2001;Vilatoba et al, 2005). 4-PBA reduced inflammatory response, apoptosis and mortality in non-steatotic livers undergoing total hepatic ischemia (Vilatoba et al, 2005).…”
Section: Antiapoptotic Strategiesmentioning
confidence: 99%
“…4-PBA reduced inflammatory response, apoptosis and mortality in non-steatotic livers undergoing total hepatic ischemia (Vilatoba et al, 2005). The addition of TUDCA to UW preservation solution protected non-steatotic livers, specifically sinusoidal lining cells and hepatocytes against cold ischemia injury (Falasca et al, 2001). Recent studies indicated that PBA, and especially TUDCA, reduced inflammation, apoptosis and necrosis, and improved liver regeneration in both steatotic and non-steatotic livers in partial hepatectomy under vascular occlusion.…”
Section: Antiapoptotic Strategiesmentioning
confidence: 99%
See 1 more Smart Citation